2004
DOI: 10.3168/jds.s0022-0302(04)73163-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Physical, and Sensorial Characteristics of “Terrincho” Ewe Cheese: Changes During Ripening and Intravarietal Comparison

Abstract: The objectives of this study were to monitor the changes in chemical [moisture, acidity, pH, and water activity (a(w))] and physical (color and texture) parameters of "Terrincho" ewe cheese during 60 d of ripening, and to determine the correlations between the changes in instrumental texture and color parameters and the ripening time of the product. Intravarietal comparison of Terrincho ewe cheese from 5 different dairy plants was performed by evaluation of mechanical parameters from texture profile analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
1
18

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(103 citation statements)
references
References 12 publications
13
71
1
18
Order By: Relevance
“…Redness (a*) resulted in a significant reduction but only in the first year. According to the literature (Dufosse et al, 2005;Pinho et al, 2005), cheese ripening led to a decrease of L*, but to an increase of b*; the difference in the results was probably due to the ripening time and to the degree of lipolysis that seemed much higher, like in other hard cheeses. L* showed a negative correlation with the protein percentage, meanwhile there wasn't a correlation with the fat content.…”
Section: Lipolysismentioning
confidence: 99%
“…Redness (a*) resulted in a significant reduction but only in the first year. According to the literature (Dufosse et al, 2005;Pinho et al, 2005), cheese ripening led to a decrease of L*, but to an increase of b*; the difference in the results was probably due to the ripening time and to the degree of lipolysis that seemed much higher, like in other hard cheeses. L* showed a negative correlation with the protein percentage, meanwhile there wasn't a correlation with the fat content.…”
Section: Lipolysismentioning
confidence: 99%
“…Different authors (OLSON, 1990;ALONSO-CALLEJA et al, 2002;CICHOSCKI et al, 2002;VOLKEN DE SOUSA;DALLA ROSA;ZACHIA AYUB, 2003;ARENAS et al, 2004;PINHO et al, 2004) found erratic evolution profiles for the pH or titratable acidity during the ripening of the artisanal cheeses. The absence of logic relationships between pH and acidity values, in Corrientes Artisanal Cheese show the influence of buffer activity, which can occur during the aging process.…”
Section: Proteolytic Changes During Ripeningmentioning
confidence: 99%
“…La composición del producto y las características de acidez, textura, color y sabor del mismo son criterios importantes de consideración inmediata al establecer su calidad y agrado (Pinho et al 2004). Un exceso de acidez puede ser causal de sabores intensos no deseables acompañados de coagulación de las proteínas y de sinéresis, generando una textura harinosa y aspecto desagradable del producto; asimismo, la acidez excesiva también podría provocar que las reacciones de Maillard se den más despacio y no se logre obtener el color característico (INA 2001).…”
Section: Introductionunclassified
“…Desde el punto de vista industrial, hay tres aspectos de la textura del dulce de leche que es necesario controlar: la consistencia, considerada en este caso como la capacidad del producto de mantenerse sin derramarse al ser extendido; el tipo de corte, que va a determinar la formación o no de hilos al separar dos porciones del producto; y, por último, la extensibilidad, que va a condicionar la uniformidad de la capa que se forme al depositarlo sobre una superficie (Pauletti et al 1992). La evaluación sensorial e instrumental constituyen en este caso las herramientas idóneas para establecer la naturaleza de las características de textura, color y sabor del producto (Pauletti et al 1992, Pinho et al 2004, HunterLab 1996.…”
Section: Introductionunclassified